2013
DOI: 10.1039/c3ib20254b
|View full text |Cite
|
Sign up to set email alerts
|

Microdevice array-based identification of distinct mechanobiological response profiles in layer-specific valve interstitial cells

Abstract: Aortic valve homeostasis is mediated by valvular interstitial cells (VICs) found in spatially distinct and mechanically dynamic layers of the valve leaflet. Disease progression is associated with the pathological differentiation of VICs to myofibroblasts, but the mechanobiological response profiles of cells specific to different layers in the leaflet remains undefined. Conventional mechanically dynamic macroscale culture technologies require a large number of cells per set of environmental conditions. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 55 publications
3
46
0
Order By: Relevance
“…44,45,106,108 These findings have potentially provocative implications linking pathological stretch with the deterioration in aortic valve tissue properties and function that occurs with disease. Indeed, Thayer et al 45 found that subjecting aortic valve leaflets to a combination of pathological stretch and pressure loads ex vivo caused a significant increase in the thickness of the fibrosa and spongiosa layers ( Figure 4C).…”
Section: Hemodynamic Effects On Aortic Vicsmentioning
confidence: 99%
See 2 more Smart Citations
“…44,45,106,108 These findings have potentially provocative implications linking pathological stretch with the deterioration in aortic valve tissue properties and function that occurs with disease. Indeed, Thayer et al 45 found that subjecting aortic valve leaflets to a combination of pathological stretch and pressure loads ex vivo caused a significant increase in the thickness of the fibrosa and spongiosa layers ( Figure 4C).…”
Section: Hemodynamic Effects On Aortic Vicsmentioning
confidence: 99%
“…However, when both tension and TGF-β1 were applied to the valve leaflets simultaneously, αSMA expression increased synergistically. Moraes et al 108 also observed interaction between stretching and TGF-β1 treatment in the activation of isolated VICs but found that synergism depended on the layer from which the VICs were isolated (ie, fibrosa versus ventricularis) and the ECM protein on which they were cultured. The link between mechanical stimulation and TGF-β1 signaling was further supported by subsequent research that implicated cell-mediated mechanical activation of latent TGF-β1.…”
Section: Hemodynamic Effects On Aortic Vicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of VIC biology, TGF-b1 and cyclic strain synergistically act to enhance VIC myofibroblast differentiation and collagen synthesis. 66,69,96 VIC response to cyclic strain is ECM protein-dependent, 69 similar to the MSC response to ECM elasticity. 26 To develop a means of delivering customized combinations of microenvironmental cues to the cells within a TEHV, there is growing interest in the use of scaffolds based on synthetic hydrogel materials.…”
Section: Regulation Of the Microenvironmentmentioning
confidence: 75%
“…Both can elicit responses associated not only with valve disease, but also development, repair, and regeneration, including increased matrix synthesis and remodeling, 6-8 and VIC activation to the secretory myofibroblast phenotype. 6,66,69 All in all, there is significant interaction between various types of microenvironmental cues, which profoundly impact cell responses. In the context of VIC biology, TGF-b1 and cyclic strain synergistically act to enhance VIC myofibroblast differentiation and collagen synthesis.…”
Section: Regulation Of the Microenvironmentmentioning
confidence: 99%